Evaluation of yield and pest and disease resistance of cocoa clones in Kolaka District, Southeast Sulawesi, Indonesia - rubiyo rubiyo; yovita anggita dewi; CHANDRA INDRAWANTO; IMRAN IMRAN; AGUS SALIM; BAHARUDIN BAHARUDIN; M.T. RATULE (Society for Indonesian Biodiversity, 2020)
Abstract. Rubiyo, Dewi YA, Imran, Salim A, Baharudin, Indrawanto C, Ratule MT. 2020. Evaluation of yield and pest and disease resistance of cocoa clones in Kolaka District, Southeast Sulawesi, Indonesia. Biodiversitas 21: 5698-5607. Cocoa is one of the main plantation commodities in Indonesia. It is an important source of foreign exchange and employment. Currently, Indonesian cocoa production and productivity, including in Southeast Sulawesi, are declining due to pests and diseases. In addition, there is a lack of high-quality and high-yielding clones. This study aimed to evaluate the quality of cocoa clones and resistance to cocoa pod borer (CPB) and cocoa pod rot (CPR) disease caused by the fungus Phytophthora palmivora. The study tested 12 cocoa clones, which included four high-yielding clones. The research location was in Lambandia Subdistrict, Kolaka District, Southeast Sulawesi Province, Indonesia. Clonal planting material was propagated by grafting in 2010. The study used a randomized block design and the treatments consisted of 20 plants of each cocoa clone with three replications. The clones were evaluated from 2018 to 2019. The observed variables included resistance to CPB and CPR. The results of the study based on the quality component showed that the clones MT, M04, and M01 had the highest average weight per one dry bean of 1.55 g, 1.64 g, and 1.24 g, respectively. Beans produced by clones MT, M01, and M04 had an average fat content of 53.36%, 52.72%, and 50.76%, respectively. Observations of the average number of pods with CPR showed that the lowest rate of attack (about 6%) was in BAL 209 and PT. Ladongi clones, with attack intensities of 20% and 18%, respectively; therefore, these clones were classified as resistant to CPR. Evaluation of the level of resistance to attack by CPB pests found two resistant clones, PT. Ladongi and Sulawesi 2, with light levels of attack on beans.